Influence of Linguistic Skills in Reading Strategies for Deaf Students - González Santamaría, Virginia; Domínguez Gutiérrez, Ana Belén (Revista de Investigación en Logopedia, 2018)
This study examined, on one hand, the relations between use of cochlear implants (CIs) and mechanisms involved in reading acquisition, in deaf children with and without CIs -specially in children with early cochlear implants-, and on the other hand, the mechanism underlying reading learning and the linguistic bases syntax and vocabulary). Some studies have shown the continuous use of the Key Word Strategy (KWS) by deaf persons. This strategy consists of indentifying some frequent content words and ignoring the function words. 172 deaf children and 797 hearing children were evaluated with a reading level test and three tasks that evaluate the type of strategy involved in reading, and the syntax and vocabulary knowledge. The results show that deaf children, including the group of children with early cochlear implants, do use the Key Word Strategy. This use is due to have a linguistic deficiency and a poor ability to deal with function words. The degree of hearing loss for children who use CIs, the age of implantation and the reading level (in all of deaf groups) play an important role in using the Key Word Strategy. In this situation, some pedagogical consequences are considered.